Side effects may vary - Murphy, Julie, 1985- (New York, NY : Balzer + Bray, an imprint of HarperCollinsPublishers, 2014)
"Alice is ready to go out in a blaze of glory, but then she discovers she's in remission from cancer and she must deal with all of the mistakes she's made and the people she's hurt"--
Keywords: Leukemia -- Juvenile fiction; Revenge -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Romance fiction; Friendship -- Juvenile fiction; Leukemia -- Fiction; Revenge -- Fiction; Interpersonal relations -- Fiction; Love -- Fiction; Friendship -- Fiction; Young adult fiction